SOCIALLY-ORIENTED MODEL OF ECONOMIC DEVELOPMENT AS THE BASIS FOR THE CONSOLIDATION OF SOCIETY - KALACH, Hanna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The social, institutional and economic system of Ukraine has been in a state of instability for quite a long time. Before the start of the full-scale war with russia, Ukraine ranked alongside third world countries in international economic rankings. The effectiveness of the development of financial provision of social capital in Ukraine has long been indicative of negative changes in the structure of expenditures for social support and protection of the population. The article proposes a socially-oriented model for the revival of the economy of Ukraine, which is based on partnership relations, strengthening the institutional model, which would not oppose the freedom of individual individuals to act according to their own values, goals and preferences, and would contribute to overcoming poverty and reducing the distance of population stratification. Characteristic features of the model of socially-oriented development is identified, among which it is worth highlighting the presence of institutions of socially responsible entrepreneurship; overcoming poverty of the main masses of the population; social protection of the poor; the presence of informal institutions that control socio-economic processes; reduction of disparities in the level of income of the population. It is proven that in difficult times, the consolidation of society is the main strategy of the state, since the "social" element of the model refers to the support of equal opportunities and the protection of those who cannot enter the free labor market due to old age, disability and/or unemployment, the ultimate goals of development economy consist in the harmonious coordination of individual and public interests. The basic principles for creating the conditions of such a model have been determined: the rule of law and private autonomy, ensuring the monetary order, forming an open competitive environment, and institutionalizing group interests.